Feasibility of using ultra-high ductility cementitious composites for concrete structures without steel rebar. (1st September 2018) - Yu, Kequan; Li, Lingzhi; Yu, Jiangtao; Xiao, Jianzhuang; Ye, Junhong; Wang, Yichao
Highlights: UHDCC has the tensile strength from 5MPa to 20 MPa with tensile strain from 8% to 12%. Plain UHDCC beam tests demonstrated the adequate loading capacity and ductility. Feasibility of using plain UHDCC in structure without steel bar was confirmed. Abstract: To verify the feasibility of using the ultra-high ductility cementitious composites (UHDCC) for construction without steel reinforcement, the mechanical properties of UHDCC was experimentally tested at material, structural member and structure levels. The tensile strength of UHDCC was from 5 MPa to 20 MPa, the average tensile strain capacity was 8% with the maximum value up to 12%. Four-point bending tests demonstrated that the plain UHDCC beams can match the loading capacity of conventional reinforced concrete beams with the steel reinforcement ratio of 0.5–1.5%. The deflection-span ratio of all the plain UHDCC beams exceeded 1/50 at the peak load. The eccentric compressive loading tests showed that the loading capacity of plain UHDCC column was close to that of RC column with a steel ratio of 0.8%. Additionally, shaking table tests were implemented on a RC frame (steel reinforcement ratios of columns were about 2.0%) and a plain UHDCC frame. The UHDCC frame survived 3 kinds of earthquakes with the peak ground acceleration from 0.105 g to 1.178 g, and exhibited excellent inter-story drift control under extremely strong earthquakes. The performance of the UHDCC frame fulfilled the requirements of various seismic codes. The feasibility of non-steel reinforced UHDCC structure was preliminarily confirmed by this study.